Application of Cow Manure and Dolomite on Mung Bean (Vigna radiata L.) Plants - Roswita Oesman; Rahmaniah Rahmaniah; Asmah Indrawati; Abdul Rahman (Universitas Sebelas Maret, 2024)
The plant growth and yield could be influenced by the soil ameliorants. This study was to obtain the effect of cow manure, dolomite, and their interactions on the growth and yield of mung bean plants. This study was conducted at Marindal II Village, Patumbak Subdistrict, Deli Serdang District, North Sumatra from February to May 2022. A factorial randomized block design was selected in this study with the first factor being the dosage of cow manure (0; 2.5; 5 tons ha-1) and the second factor was the dolomite lime (0; 1; 2 kg plot-1) within three replications. Data were analyzed using ANOVA and further tested by Duncan at P<0.05. The results showed an increase in dry weight, seed weight plot-1, 100-seed weight, and yield ha-1 of mung bean were found in 5 tons ha-1 of cow manure dose by 19.06%; 103.62%; 6.48%; and 2.04 times. The plant height and dry weight of mung bean as well as soil pH also increased in 2 kg plot-1 of dolomite dose were 24.55; 15.68; and 7.68%. Their interaction of cow manure and dolomite had a slight impact on the growth and yield of mung bean plants